Isolation, characterization, and localization of heparin-binding growth factors in the heart. - Casscells, W (1990)
Acidic and basic fibroblast growth factors (aFGF and bFGF) are angiogenic polypeptide mitogens for cells of mesodermal and neuroectodermal origin. In this report we describe the purification from several normal human hearts (including a very fresh, nonischemic sample) of heparin-binding, acid-, heat- and trypsin-sensitive 14-18-kD peptides that crossreact with antisera against aFGF and bFGF. Further evidence includes (a) prevention of mitogenicity by protamine and by anti-bFGF, (b) displacement of 125I-bFGF from cell membranes, and (c) stimulation of capillary endothelial cell migration. Specific immunohistochemistry localized bFGF to endothelial cells and, surprisingly, to cardiac myocytes, with almost no immunoreactivity in smooth muscle cells. These peptides may function in cardiac embryogenesis, hypertrophy, atherogenesis, angiogenesis, and wound healing, and may also have endocrine, neurotropic, or vasomotor functions.